Intergenerational monitoring in clinical trials of germline gene editing. Issue 3 (31st August 2019) - Cwik, Bryan
Abstract : Design of clinical trials for germline gene editing stretches current accepted standards for human subjects research. Among the challenges involved is a set of issues concerning intergenerational monitoring— long-term follow-up study of subjects and their descendants. Because changes made at the germline would be heritable, germline gene editing could have adverse effects on individuals' health that can be passed on to future generations. Determining whether germline gene editing is safe and effective for clinical use thus may require intergenerational monitoring. The aim of this paper is to identify and argue for the significance of a set of ethical issues raised by intergenerational monitoring in future clinical trials of germline gene editing. Though long-term, multigenerational follow-up study of this kind is not without precedent, intergenerational monitoring in this context raises unique ethical challenges, challenges that go beyond existing protocols and standards for human subjects research. These challenges will need to be addressed if clinical trials of germline gene editing are ever pursued.